Women Teaching Law: Stories of activism and sorority in England and Germany (ex æquo, 2023)
Women Teaching Law: Stories of activism and sorority in England and Germany Law studies currently have a strong presence of women students. What about the professors? Based on two case studies, this article discusses the conditions and impacts of female Law teaching. Its main argument is that the entrance and presence of women Law professors in universities was made possible, from the beginning, by a supportive network of colleagues within and outside academia, benefiting from the struggles of the feminist movements, the cooperation of male allies and political windows of change. Nowadays, the neoliberal university makes team work harder by promoting competition at all levels and isolating their staff. At the same time, it devalues subjects and fields of research that do not have an immediate translation in employability and financial sustainability indicators.
Keywords: feminist jurisprudence, women Law professors, case studies, Germany, England